Funções no ensino médio: história e modelagem - Souza, Valdirene Rosa de (2011)
This research has goal to address the functions in high school through relation established between the history of mathematics and the use of modeling in teaching mathematics. For that we deal with the aspects of the history of mathematics concerning the issue of change in motion, as discussed by Nicole Oresme (1323-1382). The research led us to understand that the development of mathematics is related to current events in the society and the various areas of knowledge. In our view, the study of this relation allows the construction of meaningful knowledge, and ability to generate decision-making statements that enable the consistent training of the individual and their preparation for social life